DIAGNOSIS DAN TATALAKSANA SINDROM NYERI MYOFASIAL - Stella; Sekplin A. S. Sekeon; Melke J. Tumboimbela (Jurnal Sinaps, 2021)
Myofascial pain syndrome is characterized by regional pain originating from hyperirritable spots located within taut bands of skeletal muscle, known as palpable myofascial trigger points (MTrPs).1,2,3 It affects a majority of the general population, impairs mobility, causes pain, and reduces the overall sense of well-being4.Reliably establishing the prevalence of MPS proves to be challenging, as there are no widely accepted diagnostic criteria.5 Trigger points are thought to occur as a result of muscle overuse ormuscle trauma or psychological stress. Myofascial pain syndrome is collection of the sensory, motor, and autonomic symptoms that include local and referred pain, decreased range of motion, and weaknes4.The reliability of MTrP diagnosis has long been a debatable point in the medical literature, because there had been no laboratory or imaging technique that was capable of confirming the clinical diagnosis.3 A careful history and physical exam remain the cornerstone of effective diagnosis5. Reating the underlying etiology is currently the most widely accepted strategy for MPS therapy. If the root cause is not properly treated, MTrPs may reactivate and MPS may persist.1 Various methods of MTrP treatment are available but there are currently no clinical guidelines so clinicians are required to balance the evidence, their clinical experience and the patient’s preferences.6